Enhancing the Performance of Desk Evaluation: Final Project Web Application through Back-End Maintenance - Himawan, Naufal Aqil; Kusumasari, Tien Fabrianti; Utama, Nur Ichsan (The Indonesian Journal of Computer Science, 2023)
Software maintenance resolves issues in development, including web applications. The web application can be split into front-end and back-end perspectives. Performance improvements can be achieved through back-end maintenance. Web applications with MVC (Model-View-Controller) architecture are maintained via code adjustment in the controllers. This research focuses on maintaining the back-end side of the Desk Evaluation, a web application for the university's final project management. The Collaboration Model of Software Development is the method used in this research. The controllers of the Desk Evaluation application that have been maintained are tested using unit and load testing. Unit testing shows that controllers give a proper response. Load testing indicates a 98% success rate and under 30 seconds average load time for all controllers. Then, the code in the controllers is analyzed with SonarQube, earning an A rating for reliability, signifying rule compliance, and minimizing bugs.